The Application of Computer BIM Technology in Prefabricated Construction Project Management - Nan Li (International Journal of Informatics and Information Systems, 2022)
The construction industry is a pillar industry of the national economy, and it occupies a pivotal position in our country's economic development. With the rapid development of the construction industry today, traditional construction methods can no longer satisfy the use of information, data and resources in the management of construction projects. It is necessary for BIM technology to be applied to the management of prefabricated construction projects. In order to expand the scope of application of BIM technology in construction projects and enhance people's trust, this paper studies the application of computer BIM technology in prefabricated construction project management. This article mainly uses theoretical analysis, comparative analysis and statistics to deepen the understanding of BIM technology, discovers the characteristics of traditional construction methods and construction methods supported by BIM technology, and studies the application in construction project management. The survey results show that the scope of application of BIM technology in our country's construction industry is becoming wider and wider. After five years of development, the application rate of BIM in most areas has increased by more than 10%.